THE EVOLUTION OF EMERGING MARKET (EM) SOVEREIGN CDS SPREADS DURING COVID-19 - Dr Nadir Oumayma, Pr Daoui Driss, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The COVID-19 is expected to hit emerging markets particularly hard, as many containment measures have been found to be less effective in the context of emerging markets. This study examines emerging market sovereign CDS spreadsduring the pandemic and assesses the relative importance of global factors, sovereign fundamentals, COVID-19 mortality, and policy responses. The analysis suggests that while emerging market sovereign CDS spreads can be explained by regional and global risk factors prior to COVID-19, they were determined by fiscal space, commodity revenues, and mobility dynamics during the pandemic, but not directly by changes in country-specific of the pandemic mortality rates. This case study compares the importance of dominant market factors relative to COVID-19 dynamics and policy responses to explain the daily evolution of emerging markets (EM) sovereign CDS spreads in the first half of 2020.